A Human Genomic Library Enriched in Transcriptionally Active Sequences (aDNA Library) - Pelling, Anna L. (Cold Spring Harbor Laboratory Press, 2000)
Core histone hyperacetylation, in particular of H4, is concentrated in the promoter–upstream regions of active genes and in certain cases is locuswide. Antibodies to hyperacetylated H4 were used to immunoprecipitate dinucleosomal chromatin derived from K562 human erythroleukemic cells by micrococcal nuclease digestion. The extracted DNA was made into a genomic library and was expected to contain sequences from genes active in K562 cells (an active, ‘aDNA’ library). Clones (180) were randomly selected from the library; 24 of 103 tested (23%) contained highly repeated sequences, as determined by their hybridization to total genomic DNA, and were not analyzed further. An additional 10 clones (6%) were shown to contain no insert DNA. The remaining 146 were sequenced and compared with the nucleic acid databases and in all six frames to the protein databases: Sixeen clones could be assigned to known genes, the majority of which (12) were tissue specific. All but 2 of these 16 corresponded to segments 5′ of the coding sequences, as expected if H4 acetylation is concentrated at promoter regions. Thirty-three clones (23%) displayed high sequence identity to cDNAs in the expressed sequence tag database (dbEST). Northern blots and reverse transcription (RT)—PCR were used to determine the proportion of clones representing sequences expressed in K562 cells: Although only 1 of 34 tested clones showed a band in Northern hybridization, RT–PCR demonstrated that at least 12 of 40 tested clones (30%) were present in the mRNA population. Because a further 8 of these 40 clones were identified as gene fragments by database sequence comparisons, it follows that about half of this subset of 40 clones is derived from genes. The aDNA library is thus very gene rich and not skewed toward the most highly expressed sequences, as in mRNA libraries. The aDNA library is also rich in promoters and could be a valuable source of such sequences, particularly those that lack CpG islands or other features that allow their specific selection.